Qual será a verdade do jeitinho brasileiro? Perspectivas sobre a Comissão Nacional da Verdade do Brasil - Rodrigo Stumpf González; Rodrigo Lentz (Ciências Sociais Unisinos)
After 31 years of dictatorship, military power was transferred to a civilian president for 27 years ago. A new Constitution was ratified 24 years ago and, since then, Brazil has has six presidential elections. The last three elected presidents can be considered victims of the old regime and they suffered persecutions of different natures, such as exile, imprisonment and torture. In 2012, a National Truth Commission has been implemented with the aim of establishing the memory and the truth about human rights violations committed by State agents over the past 66 years. What factors have determined it to be created now and not 20 years ago? What results can be expected of this committee? This article seeks to analyze the context and the reasons for creating the committee and its possibilities and limitations, to the theories of criminal law and transitional justice.